المشاركة بالمعرفة وأثرها على الاستغراق الوظيفي لدى أساتذة مرحلة التعليم المتوسط - براي,سمية; براي,محمد (University of Eloued جامعة الوادي, 2024)
Abstract: The current study aims to try to detect knowledge sharing and its impact on the job engagement of middle school teachers. The study sample consisted of (30) professors. To achieve this goal, we relied on the descriptive approach. We relied on the (SPSS V.25), and the study reached the following results : -There is a statistically significant effect of knowledge sharing on the job engagement of middle school teachers . -There is a statistically significant effect of sharing the intended knowledge on the job engagement of middle school teachers . - There is a statistically significant effect of sharing unintended knowledge on the job engagement of middle school teachers. تهدف الدراسة الحالية إلى محاولة الكشف على المشاركة بالمعرفة وأثرها على الاستغراق الوظيفي لدى أساتذة مرحلة التعليم المتوسط، وتكونت عينة الدراسة من (30) أستاذ وأستاذة، ولتحقيق هذا الهدف اعتمدنا على المنهج الوصفي، كما اعتمدنا في دراستنا على الاستبانة كأداة رئيسية لجمع المعلومات، ولمعالجة البيانات المتحصل عليها اعتمدنا على برنامج (SPSS V.25) ، وتوصلت الدراسة إلى النتائج التالية: - يوجد أثر ذو دلالة إحصائية للمشاركة بالمعرفة على الاستغراق الوظيفي لدى أساتذة التعليم المتوسط. - يوجد أثر ذو دلالة إحصائية للمشاركة بالمعرفة المقصودة على الاستغراق الوظيفي لدى أساتذة التعليم المتوسط. - يوجد أثر ذو دلالة إحصائية للمشاركة بالمعرفة غير المقصودة على الاستغراق الوظيفي لدى أساتذة التعليم المتوسط
دراسة ميدانية
Keywords: المشاركة بالمعرفة; الاستغراق الوظيفي; knowledge; Knowledge sharing; job engagement